2022
DOI: 10.3389/fbioe.2022.824025
|View full text |Cite
|
Sign up to set email alerts
|

Synergistically Promoting Bone Regeneration by Icariin-Incorporated Porous Microcarriers and Decellularized Extracellular Matrix Derived From Bone Marrow Mesenchymal Stem Cells

Abstract: Multifunctionality has becoming essential for bone tissue engineering materials, such as drug release. In this study, icariin (ICA)-incorporated poly(glycolide-co-caprolactone) (PGCL) porous microcarriers were fabricated and then coated with decellularized extracellular matrix (dECM) which was derived from bone marrow mesenchymal stem cells (BMSC). The porous structure was generated due to the soluble gelatin within the microcarriers. The initial released ICA in microcarriers regulated osteogenic ECM productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…The method of this part was according to Zhou's report 21 . The Ica concentration was detected by UV Spectrophotometer at 270 nm and calculated according to the standard curve (Figure S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method of this part was according to Zhou's report 21 . The Ica concentration was detected by UV Spectrophotometer at 270 nm and calculated according to the standard curve (Figure S1).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it can be used as a carrier of stem cells, growth factors, drugs, etc., further regulate the formation of new bone 19 . Tissue engineering microspheres based on PLA, PGCL, or PLGA have been widely studied for bone tissue engineering repair and achieved promising results 20–22 . Among them, PLGA, as a bone tissue engineering material approved by the Food and Drug Administration (FDA), which has good biocompatibility, adjustable biodegradability, and mechanical properties, is an ideal matrix material for bone tissue engineering 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 For example, as the primary active flavonoid phytomolecule in epimedium, icariin (ICA) was successfully incorporated in the poly(glycolide-co-caprolactone) (PGCL) microcarriers and the sustained release of ICA enhanced the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) and the repair of rat calvarial defects. 7 However, in the Balkan region of southeast Europe, an ethnobotanical analysis demonstrated that 128 plant species could be used for wound treatment, with their external forms, including decoctions, tinctures, oils, ointments, and balms, or directly for skin use. 8 In addition, it was reported that 64 plants in India have wound-healing activity and could treat various wounds such as cuts and burns.…”
Section: Introductionmentioning
confidence: 99%
“…Drug delivery is critical in bone tissue engineering. In previous studies, biopolymers and bioceramics were commonly used in the design of drug delivery systems for bone-related diseases [5][6][7][8]. Of all the materials in this category, bioactive glass (BG) is a great candidate for bone regeneration due to its biocompatibility, biodegradation, angiogenesis, bone conduction and bone-induced behavior [6].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of biomaterials with signal factors (natural medicine, growth factor, active peptide, etc.) can signi cantly improve the biological activity of the materials [5,9,10]. In recent years, many compounds derived from natural plants have shown multiple biological properties, including antioxidant, anti-in ammatory and anticancer effects.…”
Section: Introductionmentioning
confidence: 99%